Web services and service-oriented architectures the savvy manager's guide - Barry, Douglas K. (San Francisco : Morgan Kaufmann, 2003)
Web services are leading to the use of more packaged software either as an internal service or an external service available over the Internet. These services, which will be connected together to create the information technology systems of the future, will require less custom software in our organizations and more creativity in the connections between the services. This book begins with a high-level example of how an average person in an organization might interact with a service-oriented architecture. As the book progresses, more technical detail is added in a "peeling of the onion" approach. The leadership opportunities within these developing service-oriented architectures are also explained. At the end of the book there is a compendium or "pocket library" for software technology related to service-oriented architectures. Only web services book to cover both data management and software engineering perspectives, excellent resource for ALL members of IT teams Jargon free, highly illustrated, with introduction that anyone can read that then leads into increasing technical detail Provides a set of leadership principles and suggested application for using this technology.
Introduction: A business trip in the not-too- distant future. Information technology used in this trip. Service-oriented architectures and Web Services. Forces affecting the adoption of Web Services and other integration techniques. Growing impact of Web Services. Service-oriented architectures and beliefs about enterprise architectures. Starting to adopt a service-oriented architecture. Part II: Managing change needed for a service-oriented architecture: Change will happen. Tips for managing change issues during development. Part III: Creating service-oriented architectures: Architectures at each stage of adoption for Web Services. Architectural options. Middle-tier architecture. Revisiting the business trip in the not-too-distant future. Part IV: Compendium of software technology for service-oriented architectures: Additional specification details. Quick reference guide. Index.
Includes index.
Keywords: Computer network architectures; Web servers -- Management; Business enterprises -- Computer networks -- Planning; Business enterprises -- Computer networks -- Management; Intranets (Computer networks) -- Design and construction; Electronic books